Genipin Cross-Linked Decellularized Nucleus Pulposus Hydrogel-Like Cell Delivery System Induces Differentiation of ADSCs and Retards Intervertebral Disc Degeneration - Yu, Lei; Liu, Yi; Wu, Jianxin; Wang, Shuang; Yu, Jiangming; Wang, Weiheng; Ye, Xiaojian (Frontiers in Bioengineering and Biotechnology, 2021)
Intervertebral disc degeneration (IDD) is the pathological basis of disc degenerative diseases (DDD). Reduction in the number of cells and degeneration of extracellular matrix (ECM) in the nucleus pulposus (NP) are characteristics of IDD. Bio-hydrogel combined with stem cell transplantation is a promising treatment. Injectable ECM hydrogels have good biological activity and in-situ gelatinization. However, its biomechanics and stability are insufficient to provide adequate mechanical support for intervertebral discs and to maintain the long-term survival of stem cells. In our study, we developed genipin cross-linked decellularized nucleus pulposus hydrogel (GDH) as delivery system. We evaluated the mechanical properties, stability, biocompatibility and differentiation induction of GDH cross-linked with different concentrations of genipin in vitro. The GDH-loaded adipose derived mesenchymal stem cells (ADSCs) (GDHA) were injected into the rat degenerated coccygeal intervertebral disc . The effect of intervertebral disc regeneration in vivo was evaluated. The results showed that GDH with 0.02% of genipin had similar elastic modulus of human nucleus pulposus, good biocompatibility, and inducibility of expressing NP-related genes. In vivo studies shown that GDHA improved the survival of ADSCs, improved intervertebral height, MRI index, and histological grading score. In conclusion, genipin cross-linked GDH, as an outstanding bio-hydrogel cell delivery system, has the therapeutic potential for retarding IDD.